Investigation of the Geometric Characteristics of Inhalable Particles Emitted from the Process of Grinding Dental Restorations - Milana Ilic Micunovic; Igor Budak; Djordje Vukelic; Daniela Djurovic Koprivica; Milos Kuzmanovic; Boris Agarski; Tatjana Puskar (Applied Sciences, 2024)
The study concerns measurement and evaluation of the geometric characteristics of the inhalable fraction of particulate matter generated in the process of grinding dental restorations, which is a process that generates a large quantity of particulates. The research is based on measurements taken with a personal sampler, whereby the characteristics of particulates are determined based on the particle mass collected on filters. The collected filters were examined using scanning electron microscopy (SEM), and the resulting micrographs were processed through image analysis. The complex geometry of particles was examined through the analysis of 14 parameters, of which 6 define size and 8 describe morphological characteristics. Two software programs were used for the image analysis process to gather a wide range of parameters describing particle geometry. The relationship and dependence between the geometric parameters used to describe particle shape and size were investigated using multivariate analysis methods. Through correlation analysis, principal component analysis, and cluster analysis, parameter selection and reduction were performed to provide an understanding of the particles inhaled by exposed workers, which also influences the biological response of exposed organisms and the burden on the working environment.